Comparison of growth pattern, condition factor, gonadosomatic index of Manggabai (Glosogobius giuris) and Payangka (Ophieleotris aporos) in Limboto Lake, Gorontalo, Indonesia - Hasim Hasim; Jali Tuheteru; Dewi Nuryanti Fazrin (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hasim, Tuheteru J, Fazrin DN. 2021. Comparison of growth pattern, condition factor, gonadosomatic index of Manggabai (Glosogobius giuris) and Payangka (Ophieleotris aporos) in Limboto Lake, Gorontalo, Indonesia. Biodiversitas 22: 3388-3393. Manggabai and Payangka are endangered native fishes in Limboto Lake due to continuous degradation in the lake. In addition, silting lake along with its area that continues to narrow can threaten the life of both fishes although the government has stipulated restoration of Limboto Lake as the ecosystem of the fishes. However, the current information on the fishes remains considerably limited in terms of making it as a conservation strategy. This study aims to analyze the relationship between the total length and weight of Payangka and Manggabai. Furthermore, it analyzes the condition factors and the gonadosomatic index of the two fishes. The research method integrates survey and laboratory techniques. The fishes are collected by using trap made of bamboo and motorcycle tires that are installed for three days and the catches are 60 fishes including 30 Manggabai and 30 Payangka. Then the total length and weight of the fish and their gonad weight were measured. Data analysis used mathematical formulation of the relationship between total weight and length, condition factor, and gonadosomatic index. The result of the analysis shows that the growth pattern of the Manggabai was negative allometric whereas the Payangka was positive allometric. The condition factor for both types is generally less than 1.7. The gonadosomatic index of Manggabai ranges from 4.10-20.00% and Payangka ranges from 0.05-1.98%. These conditions indicate that differences in growth pattern, condition factor, and gonadosomatic index are different forms of response to environmental conditions and in the spawning season of both types of fish.